IMPLEMENTASI KEBIJAKAN PENGELOLAAN ALOKASI DANA DESA DI DESA SIBOANG KECAMATAN SOJOL KABUPATEN DONGGALA - Aswar, Aswar (Katalogis, 2017)
This study aims to find out the Implementation of Management Village Fund Allocation Policy in Siboang Village, Sojol Sub-district, Donggala RegancyBy using theory of Edward III. In this study we use 7 informants by using purposive method. Data are collected by Observation, Interview, and Documentation. The results show that Implementation of Management Village Fund Allocation Policy In Siboang Village less run well. Because the four dimensions which have been examined, explained that the four dimensions are all running less good. They are the dimensions of communication (socialization Less implemented), Resources (human resources, infrastructure and other supporting facilities are inadequate), Dimensions Desposition (less commitment) Bureaucratic structures (Coordination between related parties is less established).